Unusual flow behavior of Fe-based soft magnetic amorphous ribbons under high temperature tensile loading - Oh, Jiyun; Suh, Jin-Yoo; Kim, Woo-Jin; Jang, Jae-il; Kang, Ki Hoon; Yoon, Chong Seung; Choi-Yim, Haein (ELSEVIER SCIENCE BV, 2018)
The viscous thermal flow behavior and mechanical property of [Fe0.6Co0.15B0.2Si0.05]((100 - x)) Tax (x = 0, 1, 2, 3, 4, and 5) soft magnetic amorphous ribbons were studied. The characteristics of melt- spun amorphous ribbons were measured by using vibration sample magnetometer (VSM), nanoindentation, differential scanning calorimetry (DSC) and thermo- mechanical analysis (TMA) to study the effects of Ta content variation on the thermal stability, mechanical, and soft magnetic properties. We observed that the nanoindentation hardness, Young's modulus, and glass transition and crystallization temperatures were improved by the addition of Ta. Using dilatometry measurement, TMA, by heating at a constant rate under tension mode, we examined not only the glass transition and crystallization behaviors but also the possibility of coexistence of multiple amorphous phases. (c) 2018 Elsevier B. V. All rights reserved.
Keywords: HIGH SATURATION MAGNETIZATION; SUPERCOOLED LIQUID REGION; BULK GLASSY ALLOYS; VISCOUS-FLOW; THERMAL-STABILITY; LOW COERCIVITY; STRENGTH; A/M; TA; NI